Investigation of the densification and heat conducting enhancement measures on MIL-101 and its composite for hydrogen storage by adsorption. (26th February 2022) - Xuan, Zhang; Qing-rong, Zheng; Hong-zhou, He; Ting-quan, Sun; Zhong-gang, Zhang
Abstract: Increasing the packing density and enhancing heat conducting of MOFs systems are crucial to their practical applications. For this purpose, MIL-101 was selected and undergone the incorporation of the activated carbon (AC), the densification by mixing expanded graphite (ENG) and employing 3D printing via PVA and bentonite clay. Structural characterizations and adsorption equilibrium tests of hydrogen were conducted. The effect of a honeycomb heat exchanging device (HHED), ENG and 3D printing on the thermal conductivity enhancement was evaluated by the charge/discharge tests of hydrogen on a 0.5 L storage vessel under a flow rate of 20 L/min at 77.15 K. It shows that the specific surface area and micro-pore volume of the sample have the largest values by incorporating AC about 1 wt% but decrease in mixing ENG and 3D printing. The mean limit isosteric heats of hydrogen adsorption on the samples prepared by 3D printing are larger than those on the ENG composites. In comparing with those of addition of ENG, the HEED and 3D printing respectively prolonged the effective charge duration about 3.1%, 11.5% by cutting down the temperature fluctuation about 11.1%, 14.8%. It suggests that 3D printing is more effective on densifying the MOFs by enhancing its thermal conductivity. Highlights: Relationship between added AC, ENG, bentonite clay and the structures of the sample. Relationship between added ENG, bentonite clay and the thermal conductivity of the sample. 3D printing is a better method for the densification of the MIL-101 than mixing the ENG. 3D printing performs better on heat conducing enhancement than using heat exchanging devices.